What kind of values could be recognised in green messages, with special emphasis on children - Strasser, Verena (2015)
A lot of attention has been put on analysing why people behave in a certain way in many different aspects of life. Sustainability and environmental protection has started as early as in the 60s, but it was not until the early 90s that corporations showed serious attempts to turn towards greener business practices. Various researchers have highlighted the tremendous responsibility of companies and the role of marketing for a more sustainable society. Furthermore, it has been noted that values tend to be the base for environmental conduct, be it awareness, concern, worldview, attitude or behaviour itself. In general, it looks like that the more a person feels connected to nature, the less likely it will be that this individual will consciously destroy or damage the environment. Research has shown that children, having experienced an intense relationship with nature, will likely turn into adults with proenvironmental attitudes. Since the pace of life has dramatically speeded up, information has to be readily available and easily understood. Advertisements, in the environmental context, could provide a glimpse of latest corporate sustainable practices. Thus, my research work attempts to generally classify environmental advertisements and identify the values transmitted with the help of two different analyses, one especially developed for children. It was my greatest concern to point out the importance of children already today and their future potential by adding information to the current sustainability discussion.